Inter-relationships between chemical constituents, rumen dry matter and nitrogen degradability in fresh leaves of multipurpose trees - Nsahlai, I.V.; Siaw, D.E.K.A.; Umunna, N.N. (Wiley, 1995)
This work determined the inter-relationships between constituents, rumen dry matter (DM) and nitrogen (N) degradabilities of fresh leaves from 20 multipurpose tree (MPTs) accessions belonging to the following genera: Acacia(2), Cajanus (2), Chamaecytisus (2), Erythrina (2), Leucaena (8) and Sesbania (4). Significant differences were observed among genera in all assayed chemical attributes except hemicellulose. There was apparently no disappearance of N in A saligna after the initial solubility. All genera had similar DM and N solubility but varied in degradation rate of DM, effective degradability of DM and effective degradability of N. Except for A saligna, synchronization indices of the release of nutrients for each accession ranged from perfect (0.93) to poor (-0.31) for soluble nutrients and from moderate (0.75) to very poor (-0.81) for insoluble slowly degradable nutrients because N was in excess. Inter-relationships among chemical constituents, DM and N degradation constants were established using correlation and regression analyses. Negative correlation occured between N solubility and proanthocyanidins, N degradation rate and hemicellulose and either NDF or hemicellulose or PAs, while N degradation rate was positively correlated with N content. Equations for predicting N degradability characteristics were set. Practical implications of DM degradability and nutrient release synchrony indices in relation to basal roughage intake and microbial protein synthesis were discussed. It was concluded that a mixed model could adequately predict N degradability of fresh forages and alleviate analytical cost. A functional approach of classifying browses is outlined.